Exploring the altitude differentiation and influencing factors of PM2.5 and O3: a case study of the Fenwei Plain, China - Yin, Zhenglin; Yuan, Lei; Yang, Yulian; Wu, Xiaowei; Chen, Zhiyong; Long, Haixiao (Frontiers in Environmental Science, 2025)
Altitude differentiation has a substantial effect on the synergistic control of PM2.5 and O3 pollution. This study targets the Fenwei Plain, which is affected by mountain range blockage, divided into different altitude scales, and employs the methods of correlation analysis and geographical detector to explore the spatiotemporal heterogeneity of PM2.5 and O3 between different altitude zones and to identify the key controlling factors of pollutants between different altitude areas. The results showed that PM2.5 showed a significant decreasing trend from 2014 to 2023, whereas O3 exhibited an opposite trend. The concentrations of both pollutants decreased with increasing altitude, particularly for PM2.5, which showed significant altitudinal differentiation under the influence of topography. PM2.5 was negatively correlated with gross domestic product (GDP) and precipitation, and positively correlated with SO2. In contrast, the correlation of O3 with these factors was opposite to that of PM2.5. For spatial differentiation, NO2 and SO2 were the main factors influencing the spatial differentiation of PM2.5 and O3 at different altitudes. The explanatory power of the spatial divergence of PM2.5 and O3 was greatly increased by the interactions between the two precursors and between the precursors and meteorological factors. Furthermore, the explanatory power of the PM2.5 dominant factor increased with elevation, while the explanatory power of the O3 dominant factor was relatively high across low, middle, and high altitudes. This study serves as a guide for reducing air pollution in the Fenwei Plain and offers a novel perspective for the study of PM2.5 and O3 influenced by terrain.